Rotavirus Epidemiology and Vaccination Tactics - V. P. Bondarev; V. A. Shevtsov; I. N. Indikova; E. E. Evreinova; D. V. Gorenkov (Биопрепараты: Профилактика, диагностика, лечение, 2019)
Rotavirus infection is a widespread cause of severe gastroenteritis in children in low-income countries. Specific prophylaxis in young children has become the most important means of combating severe rotavirus gastroenteritis. The review presents current data on the molecular biology and genetic diversity of rotaviruses, interaction of viral proteins with host cell receptors, molecular aspects of infectivity and pathogenesis of rotavirus infection, and the development of immunity. It addresses a new approach to the epidemiology of rotavirus infection which regards it as a manageable infection, it illustrates the specificity of the epidemic process based on data gained from extensive experience in vaccination, and summarises relevant information on the introduction of rotavirus vaccines into the international healthcare practice. The paper summarises risks associated with the use of vaccines based on the analysis of WHO statistics, scientific publications on the epidemiology of rotavirus infection, and the results of vaccination. It analyses approaches of the competent authorities of some countries to the tactics of vaccination against rotavirus infection and the WHO stance on the use of existing vaccines for the prevention of rotavirus infection. A conclusion was made that it is necessary to further improve the tactics of vaccine prevention of rotavirus infection in Russia, to study the incidence of idiopathic intussusception, and to conduct further studies aimed at characterisation of existing and newly emerging genotypes of rotavirus.